Validação de um método analítico para a determinação de chumbo, cádmio e mercúrio em pilhas alcalinas - Schuh, Alexandra Janine (2012)
People have rampantly consumed batteries, thereby obtaining mobile, low cost and highly durable energy. However, many consumers do not recognize that these batteries may contain high level of heavy metals in their composition and so discard them inappropriately with their household trash daily. In order to minimize the problems caused by batteries to the environment, legislations have been created throughout the world. In Brazil, Resolution CONAMA 401 of 2008 established the maximum levels of toxic metals in batteries. This thesis was developed with the objective of verifying the levels of cadmium, lead and mercury in order to validate an analytical method for the determination of theses toxic metals in alkaline batteries. 193 samples of alkaline batteries collected from the Brazilian market between 2010 and 2011 were evaluated; none of the evaluated samples had cadmium levels above the allowed maximum (0.002%). However, 10 samples were found to have levels of mercury that exceeded the allowed maximum of 0.0005% and 8 of the analyzed batteries had levels of lead that were higher than the allowed (0.1%). The results obtained show a high percentage of failure (9.3%) of the samples analyzed, which indicates the necessity of controlling the use of toxic metals.